Adaptive Leadership: Navigating the Challenges of Post-Pandemic Working Arrangement - Aldila Meitiasari; Dasuki Dasuki; Fajar Piscesa; Fanddy N; Pomona Angela KM (Syntax Idea)
In the seemingly new world of work after the pandemic, managers are confronted with new difficulties in managing their teams. This research aims to answer the important research question on adaptive leadership dynamics: how do leaders steer in change? Drawing on the constantly evolving nature of flexible working environments. This paper seeks to establish the various approaches used by leaders in the current work environment. The purpose of this investigation is to provide critical recommendations to the organizational decision-makers on how to manage their employees in this post-COVID-19 world. Both quantitative and qualitative data collection methods will be employed to interview leaders in various sectors regarding the following: (1) identifying and contacting leaders who have effectively navigated the team’s post-pandemic; (2) identifying firsthand experiences and understanding of leadership strategies. The study used interviews, of which 70% were semi-structured, and the number of participants was 10. The analysis presented in this study revealed the type of leadership and their coping mechanisms, the factors that led to the activation of the coping mechanisms, and that post-pandemic, a leader’s style can be altered not only for business gain but also as a positive change for the leader themselves. The change that leaders had to undergo in post-pandemic working arrangements was diverse, and changing has never been unfamiliar to changing the leadership style. Despite the fact that our studies provide significant information regarding the main area of leadership in the management climate, there are certain aspects that deserve certain considerations. The coordination of this research is based only on middle managers, which restrains the viewpoint of our study with cross-industry background. However, there is one major limitation of the study because the study was conducted at the end of the pandemic, and therefore it may not be equally relevant as any other period of time. Therefore, the leadership phenomenon can be explored from the leader’s perspective alone, and this might result in ignoring crucial follower or any other stakeholder information. In this research, there was no other interview conducted to compare with the interview completed in this research to validate the respondent answers. In view of these, it would be appropriate to take a closer look at the leadership processes from different angles in order to gain a better appreciation of the phenomenon